DEVELOPING CRITICAL APPROACH THROUGH ANALYZING INCORRECT DECISIONS IN PERFORMING OPERATIONS ON FRACTIONS - Mamasaidova Muhabbat Abdusalom qizi; Akbaraliyeva Marjona Xurshid qizi (Modern American Journals, 2025)
This article discusses the possibilities of developing critical thinking skills based on the analysis of errors and incorrect decisions made by elementary school students when performing operations on fractions. A critical approach is explained as a process that activates the student's thinking activity, aimed not only at identifying an error, but also at its in-depth analysis, understanding its causes, and solving the problem. It is proven that students can develop mathematical thinking skills, find independent solutions to problem situations, and come up with alternative ideas based on practical examples, analytical tasks, and reflective questions.
Keywords: fractions, critical thinking, wrong decision, analysis, error, mathematical thinking.